Estimasi Simpanan Karbon pada Padang Lamun di Kawasan Pantai Karang Sewu, Gilimanuk, Bali - Vitri Lestari, Komang Indah; Hendrawan, I Gede; Faiqoh, Elok (Journal of Marine Research and Technology, 2020)
The growth of the industrial sector in many countries which is relatively fast can increase emissions from greenhouse gases (GHGs) such as carbon dioxide (CO 2 ) in the atmosphere. One of the aspects in reducing carbon gas is by maintaining forests and oceans to store carbon. One of the marine resources that is quite potential as storing CO 2 gas is sea grass beds. Sea grass has a major role, namely as a carbon sink in the ocean or known as the Blue Carbon and is used for photosynthesis. The purpose of this study was to determine the carbon stocks in sea grasses at the top of the substrate (leaves), the bottom of the substrate (roots and rhizome) and on each type of sea grass obtained at Karang Sewu Beach. Determination of sampling points is as many as 6 stations and for sea grass sampling was carried out by purposive random sampling, referring to the density of sea grass which is assumed to represent or describe the condition of these waters. This research applied the dry ashing method that was carried out by crushing the sample components at 500?C. The results showed carbon deposits on the top of the substrate (leaves) of 0.01 tons, and on the bottom of the substrate (rhizomes and roots) of 0.02 tons. The yield of carbon stocks at the bottom of the substrate was higher than the top of the substrate due to the presence of organic matter, which is stored on the substrate into a carbon absorption factor at the bottom of the sea grass under the substrate.